KEBERFUNGSIAN KELUARGA ANAK KORBAN EKSPLOITASI DI KECAMAAN SENAPELAN KOTA PEKANBARU - Muttaqin, Abdi; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This research aim to describe the function?s of the family, the identity ofxploited children, describe their psychological condition, the family integrity and social relation in the family of the exploited children. This research uses a qualitative approach using descriptive research with data collection methods using observation and interviews. the study used descriptive-analitical tecniques Data analysis. From the result of this research, it can be seen that the identity of the victims of exsploitation in this study consisted of 8 children, 7 of them are still in school and only one is not school, 5 of 8 children are exploited by other people who are not family member, while 3 of them are exploited by their own family, from the 7 family functions, the functon that has been running well is the biological function of the third and fourth subject families, in addition to this last subject (fourth subject) family there is also have an educational of and recreational functional that is already running. The psycological condition of all subject are still normal and no one has mental problem and only 2 families has whole family member , namely the third and fourth families, the social relationship within the family of the exploitated children , 3 of them are still in good condition. While in the subject number two family social relationship are not good, this is proven with the children were told to live and work with other people.Key Words: Family Function?s, Exploited Children